UNIQ: Utilization of NLP techniques in plagiarism detection system through semantic analysis using WORD2VEC and BERT - Cabalsi, Glaidelyn M.; Latina, Jeffrey V.; Sanchez, Joervy R.; Vallejo, Elnard Don M. 4 0 16; 5 (2024)
u
Undergraduate Thesis: (Bachelor of Science in Information Technology) - Pamantasan ng Lungsod ng Maynila, 2024.
Keywords: 2 -- 0; 6; 20; 20; 2